Decision Support System Feasibility for Promotion using the Profile Matching Method - Dyah Ayu Megawaty; Andris Silitonga (Journal of Data Science and Information Systems, 2023)
Human Resources (HR) is an important element in companies and agencies. In companies like PT. Petrogas Sinta Energi, with fairly good economic growth and being able to compete with other companies, a system is needed to evaluate each employee to fill a position. Decision Making System (DSS) Determination of job eligibility using the profile matching method by utilizing two aspects, namely the Aspect of Work Attitude and the Intellectual Aspect can assist the Company in measuring the eligibility of an employee to occupy a position. Technology or Website-based Decision Support Systems (DSS) can speed up and simplify the determination of employee eligibility assessments as well as computerized data that can be accessed online. The results of calculations using the profile matching method, the results of the decision support system on behalf of Asep with a value of 4.55 are obtained which are selected in rank 1.